Effect of the Nature of Donor Atoms on the Thermodynamic, Kinetic and Relaxation Properties of Mn(II) Complexes Formed With Some Trisubstituted 12-Membered Macrocyclic Ligands - Garda, Zoltán; Molnár, Enikő; Kálmán, Ferenc K.; Botár, Richárd; Nagy, Viktória; Baranyai, Zsolt; Brücher, Ernő; Kovács, Zoltán; Tóth, Imre; Tircsó, Gyula (Frontiers in Chemistry, 2018)
During the past few years increasing attention has been devoted to Mn(II) complexes as possible substitutes for Gd(III) complexes as contrast agents in MRI. Equilibrium (log KMnL or pMn value), kinetic parameters (rates and half-lives of dissociation) and relaxivity of the Mn(II) complexes formed with 12-membered macrocyclic ligands were studied. The ligands were selected in a way to gain information on how the ligand rigidity, the nature of the donor atoms in the macrocycle (pyridine N, amine N, and etheric O atom), the nature of the pendant arms (carboxylates, phosphonates, primary, secondary and tertiary amides) affect the physicochemical parameters of the Mn(II) complexes. As expected, decreasing the denticity of DOTA (to afford DO3A) resulted in a drop in the stability and inertness of [Mn(DO3A)]− compared to [Mn(DOTA)]2−. This decrease can be compensated partially by incorporating the fourth nitrogen atom into a pyridine ring (e.g., PCTA) or by replacement with an etheric oxygen atom (ODO3A). Moreover, the substitution of primary amides for acetates resulted in a noticeable drop in the stability constant (PC3AMH), but it increased as the primary amides (PC3AMH) were replaced by secondary (PC3AMGly) or tertiary amide (PC3AMPip) pendants. The inertness of the Mn(II) complexes behaved alike as the rates of acid catalyzed dissociation increased going from DOTA (k1 = 0.040 M−1s−1) to DO3A (k1 = 0.45 M−1s−1). However, the rates of acid catalyzed dissociation decreased from 0.112 M−1s−1 observed for the anionic Mn(II) complex of PCTA to 0.0107 M−1s−1 and 0.00458 M−1s−1 for the cationic Mn(II) complexes of PC3AMH and PC3AMPip ligands, respectively. In spite of its lower denticity (as compared to DOTA) the sterically more hindered amide complex ([Mn(PC3AMPip)]2+) displays surprisingly high conditional stability (pMn = 8.86 vs. pMn = 9.74 for [Mn(PCTA)]−) and excellent kinetic inertness. The substitution of phosphonates for the acetate pendant arms (DOTP and DO3P), however, resulted in a noticeable drop in the conditional stability as well as dissociation kinetic parameters of the corresponding Mn(II) complexes ([Mn(DOTP)]6− and [Mn(DO3P)]4−) underlining that the phosphonate pedant should not be considered as a suitable building block for further ligand design while the tertiary amide moiety will likely have some implications in this respect in the future.